Effects of Thymoquinone on Urotensin-II and TGF-β1 Levels in Model of Osteonecrosis in Rats - Mehmet Yilmaz; Recep Dokuyucu (Medicina, 2023)
Objectives: We aimed to investigate the therapeutic effects of thymoquinone (TMQ) treatment in osteonecrotic rats by evaluating protein levels, osteonecrosis (ON) levels, fatty acid degeneration, oxidative status, and plasma levels of Urotensin-II (U-II) and transforming growth factor-beta (TGF-β1). Materials and Methods: 40 weight-matched adult male Wistar rats were grouped as control (n = 10), methylprednisolone acetate (MPA) (n = 10), thymoquinone (TMQ) (n = 10), and MPA + TMQ (n = 10). To induce ON, 15-week-old animals were subcutaneously injected with MPA at a dose of 15 mg/kg twice weekly for 2 weeks. TMQ was injected into 15-week-old rats via gastric gavage at a dose of 80 mg/kg per day for 4 weeks. The rats in the MPA + TMQ group were administered TMQ 2 weeks before the MPA injection. At the end of the treatments, cardiac blood samples and femur samples were collected for biochemical and histological evaluations. Results: In the control and TMQ groups, no ON pattern was observed. However, in tissues exposed to MPA, TMQ treatment resulted in significantly decreased ON levels compared to the MPA group. The number of cells that were positive for 8-OHdG and 4-HNE was significantly lower in the MPA + TMQ group than in the MPA group (p < 0.05). In terms of TGF-β1 and U-II levels, we observed that both TGF-β1 (367.40 ± 23.01 pg/mL vs. 248.9 ± 20.12 pg/mL) and U-II protein levels (259.5 ± 6.0 ng/mL vs. 168.20 ± 7.90 ng/mL) increased significantly in the MPA group compared to the control group (p < 0.001). Furthermore, TGF-β1 (293.50 ± 14.18 pg/mL) and U-II (174.80 ± 4.2 ng/mL) protein levels were significantly decreased in the MPA + TMQ group compared to the MPA group (p < 0.05 and p < 0.01, respectively). There was a statistically positive correlation (p < 0.05) between the TGF-β1 and U-II protein levels in all groups (p = 0.002, rcontrol = 0.890; p = 0.02, rTMQ = 0.861; p = 0.024, rMPA+TMQ = 0.868) except for the MPA group (p < 0.03, rMedrol = −0.870). Conclusions: As far as we know, this is the first study to demonstrate the curative functions of TMQ on ON by causing a correlated decrease in the expression of U-II and TGF-β1 in the femoral heads of rats.